2014
DOI: 10.1111/voxs.12106
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Technology (NAT) testing for blood screening: impact of individual donation and Mini Pool – NAT testing on analytical sensitivity, screening sensitivity and clinical sensitivity

V. Shyamala

Abstract: Globally, in a number of countries the donated blood is screened for serology markers for the Human immunodeficiency diseases-1/2, the Hepatitis C virus (HCV), and the Hepatitis B virus (HBV). Several medium human development index (HDI) countries with reasonably high percentage of transfusion transmitted infections (TTI) are evaluating nucleic acid technology (NAT) assays to detect these viruses. Serology assays are performed on individual samples, while NAT is performed on either the individual donation (ID)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…frequently not confirmed by repeat testing, or by testing for alternative markers [7,22,23]. The sensitivity of some of the ELISAs used in India is also suboptimal as is illustrated in our study where 10 out of 15 HCV WP NAT yields turned out to have detectable antibody by CLIA and seven of them also on retesting by a second more sensitive ELISA (data not shown).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…frequently not confirmed by repeat testing, or by testing for alternative markers [7,22,23]. The sensitivity of some of the ELISAs used in India is also suboptimal as is illustrated in our study where 10 out of 15 HCV WP NAT yields turned out to have detectable antibody by CLIA and seven of them also on retesting by a second more sensitive ELISA (data not shown).…”
Section: Discussionmentioning
confidence: 66%
“…The Punjab Province in India is near the border of Pakistan where two recent minipool NAT blood screening studies reported similar (or even higher) HBV and HCV yield rates than in our study, although NAT confirmation testing procedures differed. The serologic reactivity (in mainly first‐time donors) in India and Pakistan is frequently not confirmed by repeat testing, or by testing for alternative markers . The sensitivity of some of the ELISAs used in India is also suboptimal as is illustrated in our study where 10 out of 15 HCV WP NAT yields turned out to have detectable antibody by CLIA and seven of them also on retesting by a second more sensitive ELISA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the hyper‐endemicity of HIV and HBV in Namibia at the time which was 16·8% for HIV and >8% for HBV , NAMBTS decided to keep TTI testing at SANBS to benefit from the ID‐NAT screening. Like many small economies, adding NAT to blood screening was not affordable for Namibia, but necessary for established blood safety measures and had to be adopted at all cost . Relocating blood screening with ID‐NAT to Namibia at that time was not cost‐effective for a small blood service such as Namibia which was collecting a volume of 18 000 blood donations annually.…”
Section: Introductionmentioning
confidence: 99%
“…In , there is an error in Table 3 on page 320. The HIV‐1 value (7th column) for the bottom row should read ‘1600’ instead of ‘11600’.…”
mentioning
confidence: 99%